Modeling and analysis of factors affecting the integration of Beijing Tianjin Hebei low carbon economy based on SDM model - Zhu, Lin; Wu, Hua; Xu, Ying (Frontiers in Energy Research, 2023)
Guided by the goal of carbon peaking and carbon neutralization, China's economic development is facing unprecedented challenges. Studying the integrated development of regional low-carbon economy has important strategic significance and value. The harmonious growth of Beijing Tianjin Hebei(Jing-Jin-Ji) has become a national strategy, and its importance is highlighted. Promoting the regional economic integration of Jing-Jin-Ji is the most important thing to promote the integrated growth of Jing-Jin-Ji at present, and the key to realize the coordinated development and mutual benefit of Jing-Jin-Ji. In this case, this article studies a fuzzy control assessment algorithm of regional economy combined with SDM model, realizes the prediction of Jing-Jin-Ji low carbon economic expansion, and then puts forward the development strategy of Jing-Jin-Ji low carbon economic integration. The ranking of regional competitiveness of fuzzy control assessment method is in line with the reality of today's economic expansion, and the application of fuzzy rules improves the assessment speed, accuracy and objectivity. The final experiment shows that the accuracy of the proposed algorithm is high, reaching 95.14%. Moreover, the algorithm has higher efficiency and better performance. The results show that the fuzzy control assessment algorithm of regional economy can well predict the growth of Jing-Jin-Ji economy. Then this article puts forward the development strategy of Jing-Jin-Ji low carbon economic integration, in order to further promote the integrated growth of Jing-Jin-Ji and promote the adjustment and optimization of China's economic structure.